GENDER CONSIDERATION IN TECHNOLOGY DEVELOPMENT AMONG SMALLHOLDER FARMERS IN NORTHERN REGION, GHANA - Abujaja, A. M.; Obeng, F.; Apusigah , A. (UDS International Journal of Development, 2022)
Mass transfer of technology without understanding the special place of gender has often been received with mixed feelings, resulting in its misuse and its application. This paper presents results on gender consideration in the development of three maize and soybean technologies developed and promoted by Savannah Agricultural Research Institute (SARI) among 534 smallholder farmers in four selected districts in Northern region, namely West Mamprusi, Sawla-Tuna-Kalba, East Gonja and Zabzugu districts. Questionnaire, interview guide and desktop review were used as tools for the data collection.Â  Descriptive statistics and Pearsonâ€™s Chi-square test were used to analyse the data. The results revealed that generally very little attention was paid to gender issues in technology development with a p-value of 0.308 signifying that the gender of the respondents was independent of their involvement in technology and that there is no statistically significant association between gender and involvement in technology. Focused Group Discussions (FGDs) indicated that women farmers hardly come in contact with researchers and extension agents, as such their concerns with regards to technology preference and suitability were not considered. It is recommended that deliberate efforts be made during technology development to engage smallholder farmers in the identification and documentation of local needs regarding technologies so as to specifically include male and female expectations in the development of technologies. Keywords: Gender, Technology, Technology Development, Farming System Approach